STRATEGI KOMUNIKASI POLITIK PARTAI DEMOKRASI INDONESIA PERJUANGAN DALAM MEMOBILISASI PEMILIH PADA PEMILU LEGISLATIF DAERAH KOTA SEMARANG TAHUN 2014 - Ridho Satrio Hutomo; Susilo Utomo; Fitriyah . (Journal of Politic and Government Studies, 2015)
ABSTRACTThis Skription aper entitled "Political Recruitment Analyse: Studies on New MemberRecruitment of DPC PDI Perjuangan Semarang Year 2012-2013". Compiled byMuhammad Agam Ashari, NIM: 14010110130113, Social Science Program andPolitical Science under the guidance of Setiyono Budi, S. Sos, M.Pol.Admin, Ph.D.,and Dra. Rina Martini, M.Sc.Political Communication is the most important ones in every proses on sosialization of political party such as Campaign,etc. Every political party needed some of political communiation process. The research aims to determine how political communication strategy of the party, especially the Partai Demokrasi Indonesia Perjuangan (PDI-P) in the city of Semarang. In this 2014 legislative elections in the city of Semarang some unique phenomena related to the PDI-P. Semarang city has a head of government of the PDI-P but not able to win in 2009 has now managed to win with a cost that is high. PDI-P previously sizeable acquisition in 2004 sank in 2009 and now in 2014 they won an absolute. Therefore conducted research related to political communication strategies PDI-P in Semarang to mobilize voters in 2014.The research uses the theory of political communication from Maswadi Rauf, a process and activities shaping political attitudes and behavior that are integrated into a political system by using a set of symbols which means involving political messages and political actors, or associated with power, governance and government policy. Data collection techniques are observation and interviews were then processed and analyzed qualitatively. In the interview data collection conducted at PDI-P party functionaries Semarang, Legislative PDI-P Semarang, participants PDI-P Semarang.The results of this study are: (1) political communication strategy of PDI-P use strategy or method of face-to-face (2) actors who play an important role is the Chairman of the PDI-P, functionaries and party cadres, legislative candidates, and successful team of legislative candidates. (3) supporting factor is the party machine, big name party, social and political history of Semarang City community, regional cadre of behavioral effects of Semarang, Jokowi Effect. (4) Factor obstacle is lack of infrastructure, high levels of political apathy community Semarang.In doing political communication strategies PDI-P were pretty good, but in some sectors still needs to be improved is in the delivery of communication patterns. The high number of Abstentions in Semarang should be resolved with communication patterns and approaches are more varied with the aim of getting closer to the community, for example by holding a public market, the implementation of shadow puppets, and other social activities.3Expected with the implementation of the activities of the people will tend to change references and choose PDI-P.Keywords: Strategies of Political Communication, Political Party, PDI-P, legislative elections in 2014 in the city of Semarang, Semarang City Community Mobilization.